Using Hydrological Mapping to Evaluate the Effectiveness of the Bener Dam Development in Reducing Flood Risk in Purworejo Regency, Central Java - Sudaryatno Sudaryatno; Bagus Wiratmoko; Winanda Winanda; Shelly Yeni Saputri (Forum Geografi, 2020)
The Bogowonto Hulu sub-watershed has high flooding potential, especially during the rainy season. This flooding causes physical, social, and economic losses for the local community and so the Bener Dam was built to reduce the volume of flooding in the area. This research aims to find out the effectiveness of the Bener Dam in overcoming the problem of flooding around the Bogowonto Hulu sub-watershed. The effectiveness of dams can be analysed by comparing the volume of the dam reservoir with the peak discharge amount generated. The value of peak discharge can be obtained using remote-sensing data and mathematical calculations following the rational method. Using this method, the estimated peak discharge value obtained for the watershed was 302.3 m3/s while the value of dam capacity was only 210 m3/s, giving 92.3 m3/s of flooding potential. It is necessary to reduce the potential for flooding by building an IR reservoir in the catchment area, so that rainwater is accommodated rather than being immediately depleted, and to reduce concentration time.